ANALISIS FILOSOFIS TERHADAP HUKUM WARIS BAGI ANAK BEDA AGAMA DI INDONESIA: PERSPEKTIF ONTOLOGI, EPISTIMOLOGI, DAN AKSIOLOGI - Linda Anastyapatika Sari; Fitra Syari (Al-Usroh, 2025)
The issue of inheritance law for children of different faiths in Indonesia presents a serious dilemma between adherence to religious norms and the demands of social justice in a pluralistic society. This phenomenon reflects a fundamental tension between the principles of Islamic sharia, which textually prohibit interfaith inheritance, and the social reality of increasingly heterogeneous modern families. This study aims to analyze this issue in depth through a philosophical approach, focusing on three main dimensions: ontology (the essence of inheritance law), epistemology (the source and basis of legal truth), and axiology (the goals and values to be achieved). The research method employed is qualitative with a juridical-philosophical approach, integrating analysis of the Indonesian Civil Code (KUH Perdata), Compilation of Islamic Law (KHI), and literature on legal philosophy. Data collection techniques were carried out through library research from various primary and secondary sources, including fiqh texts, legislation, academic journals, and court decisions. Data was then analyzed using deductive content analysis. The findings indicate a significant discrepancy between formal legal rules and social practice, where courts often grant inheritance shares to children of different faiths through the mechanism of wasiat wajibah to uphold justice and public welfare. This highlights the need for an integrative approach that considers not only legal texts but also social, cultural contexts, and constitutional values such as Pancasila and the 1945 Constitution. This study contributes a new perspective to the discourse on inheritance law in Indonesia, offering a philosophical framework to build more inclusive and adaptive legal harmonization in response to diversity.